Valutazione economica dei costi associati al trattamento di pazienti in ossigenoterapia a lungo termine, con o senza monitoraggio telemetrico domiciliare - Ravasio, Roberto; Negro, Roberto W. Dal; Lucioni, Carlo (Farmeconomia. Health economics and therapeutic pathways, 2005)
Long term oxygen treatment (LTOT) represents an helpful, even though costly, therapeutic strategy for managing severe chronic respiratory diseases at home. The aim of the present study was to assess the economic impact of adding the home telemetric monitoring of some vital signs to the traditional domiciliary LTOT in this kind of patients. Two samples of severe chronic respiratory patients (COPD patients in 89% of cases, managed at home without, n=20, and with, n= 61, telemetric home monitoring) were compared for a 24-month period, and the corresponding outcomes measured. In the tele-monitored group of subjects, both the mean number and the mean duration of hospitalisations dropped along the two-year study, together with the n. exacerbations/ patient/year. The mean annual cost for the tele-monitored group of patients was lower by 28% in the first year, and by 33% in the second year of the study. The home tele-LTOT management of patients with severe chronic respiratory disease, mostly COPD, allows a better clinical control of the disease, with a corresponding 50% reduction of exacerbations leading to hospitalisation. Finally, the home tele-LTOT contributes substantially in minimizing the economic impact of these severe chronic respiratory diseases.